Multidisciplinary Teams on the Battlefield: An Innovative Approach to Overcrowded Field Hospitals and Trauma Centers - Mohammad Javad Behzadnia (Baqiyatallah University of Medical Sciences, 2018)
Many years ago, clinicians worked in various fields of medicine, and they made the vast majority of medical judgments and procedures. Today, the increasing population and growth in medical sciences has resulted in the development of many new medical subspecialties. Commonly, medical treatment begins with a general practitioner and progresses to a specialist in cases of complexity. Atypically, a clinician may confront an emergency situation that requires prompt action in order to save the victims. A crowd disaster at a mass gathering could easily change the normal condition of a hospital into one of crisis. This may be more apparent when it occurs on a battlefield with few medical personnel. In other words, if triage is not properly managed in an acute care setting, the other steps of the survival chain would soon be disrupted. Having organized behavior in medical teams could save time and increase efficacy.